Book Review âReasoning Techniquesâ (Malay Version) - Pinang, Pulau (Social Science Learning Education Journal, 2017)
Written by Lok Chong Hoe, titles that are discussed in this book is not a course on formal logic (or logic oriented symbols). It is aimed at selecting and discuss some of the techniques and skills from the field of logic that has broad application. Techniques and skills that can help those who follow this field to think more clearly, distinguishing about it (or opinion) different, argue correctly and effectively, analyze and evaluate the arguments presented by others, identify Fallacy contained in a weak argument and more. To achieve these objectives, the course will concentrate on such things as the difference between the possibility of logic with the possibility of physical (as the ability to think and argue logically depends on the pattern of reasoning is correct and effective. This technique does not rely on facts or the difference between a true statement with untrue statements even though it has application to a field that examines the phenomenon that exists or occurs in the world, including the study of social sciences, human history, and the arts), the argument deductive patterned syllogism, distinguish between arguments syllogism valid with unauthorized use of a Venn diagram as a way to determine the validity of an argument, the difference between the validity of the authorization, the argument deductive patterned modus ponens and modus tollens, correlation logic between representations (such as affinity patterned contrary, contradiction, contradictory, implications, subcontrary, consistency, etc.).